Indonesia's Involvement in the Paris Agreement on Low Carbon Development Agenda in Indonesia: A Social Legal Study - Thoriq Al Hakim Faizy; Radian Salman; Arif Rahman Hakim (Rechtenstudent, 2025)
Indonesia's participation in the Paris Agreement has created opportunities for international cooperation that can support the progress of low-carbon development at the national level. The participation, along with the strong global commitment to help developing countries achieve their emission reduction targets under the Paris Agreement, brings several benefits for Indonesia in obtaining international support for climate change adaptation and mitigation, including climate finance, technology transfer, and capacity building. This research aims to analyse the strategic role of the Paris Agreement towards a low-carbon development agenda in the energy sector in Indonesia. This research is based on regime theory and neoliberal institutionalism paradigm as the theoretical framework for analysing the issues addressed. Furthermore, this research applies the literature study method by using sociolegal approach. The findings of this research indicate that the Paris Agreement has contributed to the progress of low-carbon development in Indonesia particularly in the energy sector. However, its implementation has been sluggish in meeting the targets for climate change mitigation and adaptation.